2008
DOI: 10.1111/j.1743-6109.2008.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Retrieval of a Penile Prosthesis' Rear-Tip Extender

Abstract: Introduction The renewal of penile prosthesis is a foreseeable intervention because of the limited survival time of the different implants. It usually becomes necessary simply for material fatigue after long-term regular use; in some cases, premature intervention might be necessary because of infection or other perioperative complications. Aim In the case presented here, the removal of a Dynaflex penile prosthesis showed a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Checklists are widely used in the aviation industry, and serve as a reminder of items required, things to be done, or issues to be considered . While some of the items on a checklist may seem intuitive, the adoption of this methodology in the operating room is now showing great promise in improving patient safety .…”
Section: Discussionmentioning
confidence: 99%
“…Checklists are widely used in the aviation industry, and serve as a reminder of items required, things to be done, or issues to be considered . While some of the items on a checklist may seem intuitive, the adoption of this methodology in the operating room is now showing great promise in improving patient safety .…”
Section: Discussionmentioning
confidence: 99%
“…The most common complication reported with a rear tip is when it is left behind either during revision/ removal surgery or during re-positioning. Many series and case studies have been published regarding methods of RTE removal, including using a nasal speculum, graspers, a Silastic penile measuring rod, a Brooks dilator and cystoscopic (using a cystoscope in the corpora) removal [17][18][19][20][21]. Complete bilateral dislocation of the rear tips has also been reported [22].…”
Section: Complications Of Rear Tip Extendersmentioning
confidence: 99%
“…The use of rear tips may also vary by the surgical approach for prosthetic placement. A multi-institutional study showed that penoscrotal approach to prosthesis placement was associated with increased proximal dilation (10.1 cm vs 8.6 cm, P < 0.0001), and resulted in longer RTEs (1.9 cm vs 1.2 cm, P < 0.0001), when compared to infrapubic placement [20]. This difference may be because additional RTEs are added in the penoscrotal approach to place the pump lower in the scrotum.…”
Section: Current Practices In Rte Usementioning
confidence: 99%
“…This same author has even used advancement flaps and lower abdominal tissue debulking in those patients with insufficient penile length for satisfactory sexual intercourse [31]. Shaeer has described using a resectoscope to remove the corporal fibrosis scar under direct vision during penoscopy, while other authors have used penoscopy for retrieval of rear tip extenders [40–42].…”
Section: Implantation Of the Cylinders Or Rods Into The Corpora Cavermentioning
confidence: 99%